A Study to Assess the Knowledge and Attitude Regarding Physical Disability Among Students - Vinny Negi; Namita Sharma (International Journal of Trends in Humanities, 2024)
Studies suggest that college students often have a very vague knowledge regarding physical disabilities, and they tend to alter their attitude from the limited awareness without understanding the aspect in detail. It is sometimes noticed that people or even their own peers are highly neglected or are sometimes a topic of mockery. This quantitative study will consist of a structured questionnaire which will revolve around the knowledge and attitude of a student and will be used to elicit the information from the sample for further investigating the overall perception towards disabilities through method of observation and ground theory. Few students from all the years of a particular college will be closely examined with an age range from 17 to 23years.A free contact and a clarity in survey will be associated with positive attitude while a hesitant contact and an aversive survey will be categorized as negative. By the end of this study students/people will be more welcoming towards this community will make them sensitive about the way one talks about disabilities and will further compel them to introspect themselves and think about the following questions: “Are all the people disabled in one way or the other?”, “Am I ready to change my mindset and accept the disabled?” and “How do people think about themselves with respect to the disabled?”
Keywords: Clarity; Introspect; Mockery and Structured Questionnaire; perception